2004
DOI: 10.1023/b:mcbi.0000012851.42642.be
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol-sensor initiates M. tuberculosis entry into human macrophages

Abstract: Cholesterol-mediated mycobacteria entry into and survival within macrophages has added a new dimension to Tuberculosis research. The molecular mechanism through which cholesterol initiates this process is still poorly understood. The present study addressed to resolve this mechanism revealed that Mycobacterium tuberculosis possesses cholesterol-specific Receptor 'Ck'-like molecule responsible for mycobacterial entry into macrophages. Further human Receptor-Ck was found to regulate transcriptional expression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
39
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 11 publications
1
39
0
Order By: Relevance
“…paratuberculosis associates with and is internalized into THP-1 monocytes in a cholesteroldependent manner and at cholesterol-rich areas of the membrane. This, coupled with our finding of cholesterol-dependent M. bovis uptake by THP-1 cells, is consistent with other studies of pathogenic mycobacteria (12,22,32). Intriguingly, significantly fewer E. coli bacteria associated with cells as cellular cholesterol levels fell.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…paratuberculosis associates with and is internalized into THP-1 monocytes in a cholesteroldependent manner and at cholesterol-rich areas of the membrane. This, coupled with our finding of cholesterol-dependent M. bovis uptake by THP-1 cells, is consistent with other studies of pathogenic mycobacteria (12,22,32). Intriguingly, significantly fewer E. coli bacteria associated with cells as cellular cholesterol levels fell.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, cellular cholesterol may actively affect processes associated with normal bacterial clearance. One example is the cholesterol-dependent binding of the mycobacterial protein lipoamide dehydrogenase C (LpdC) to coronin-1 (also known as TACO) on the phagosomal membrane (10,12,22). Binding aids retention of the coronin-1 protein (8), which, in turn, facilitates phagosome maturation arrest (10) by blocking lysosomal delivery (21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kaul et al (2004) found that there are cholesterol receptors on the M. tuberculosis cell wall. For guiding DNAzymes to M. tuberculosis and improving the uptake of DNAzymes, we ligated a cholesterol molecular at the 3Ј-end of DZ4, but we did not observe the expected improvement.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular genetics and micro biology have shown multiple important roles for cholesterol in Mtb pathogenesis. Cholesterol is a major sterol of the mammalian plasma mem brane and is abundant in the macrophage [41].…”
Section: Key Termmentioning
confidence: 99%